Analysis of Student Interest to Continue School to Higher Education at State High School 1 Bintan Pesisir - Nauli Agustin; Haryono Haryono; Supentri Supentri (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by the interest of students to continue their studies to tertiary institutions at SMA Negeri 1 Bintan Pesisir. The formulation of the problem in this study is how high is the interest of students to continue their studies to higher education at SMA Negeri 1 Bintan Pesisir. The purpose of this study was to determine the level of students' interest in continuing their studies to higher education at SMA Negeri 1 Bintan Pesisir. This study uses a type of quantitative research. The research method used by the author is a descriptive survey method. The data collection instrument used in this study was a questionnaire consisting of 20 statements distributed to 26 respondents. Based on the results of the research regarding the Analysis of Student Interests to Continue to Higher Education at SMA Negeri 1 Bintan Pesisir, it can be concluded that the high interest of students to continue studying at SMA Negeri 1 Bintan Pesisir, this can be proven by the results of the respondents' answers, namely Strongly Agree (SS) plus Agree (S), then the results obtained from the recapitulation above are 70.93%. Thus it can be concluded that the analysis of student interest in continuing school to university at SMA Negeri 1 Bintan Pesisir is at a very good level.